(a + b)(a^2 - ab + b^2)

(a + b)(a^2 - ab + b^2) = a^3 - a^2b + ab^2 + ab^2 - ab^2 + b^3 = a^3 + b^3

Question

Asked 4/23/2013 11:34:50 AM

Updated 4/2/2017 2:17:50 AM

1 Answer/Comment

Edited by Andrew. [4/2/2017 2:16:52 AM]

Rating

3

(a + b)(a^2 - ab + b^2)

= a^3 - a^2b + ab^2 + ab^2 - ab^2 + b^3

= a^3 + b^3

= a^3 - a^2b + ab^2 + ab^2 - ab^2 + b^3

= a^3 + b^3

Added 4/2/2017 2:17:50 AM

This answer has been confirmed as correct and helpful.

27,095,113

questions answered

There are no comments.